Description of Women Image in the Story “the Cut Glass Bowl” by F. Scott Fitzgerald (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
F. Scott Fitzgerald is one of the outstanding authors of the XX century American Literature and his contribution is enormous in the development of “Jazz Age” or “Roaring Twenties” in American literature. F. Scott Fitzgerald’s works influenced significantly on the writers’ of American literature and continue to be researched today. The author chiefly described society’s traditions, way of life and cultural values in his short fiction. The story “The Cut Glass Bowl” portrays the dynamics of a troubled marriage, but it also provides insight into the portrayal of the woman character. In the paper Evylyn’s characterization is discussed and how the main character as a woman strives for material wealth, but understands that this does not bring happiness, and feels alone herself in her marriage and longs for emotional connection and freedom is analyzed.